Branding Piety and the Mediatization of Da’wah through Digital Content - Johan Faladhin; Destita Mutiara; Ulmi Marsya (Jogjakarta Communication Conference (JCC), 2025)
The rapid development of digital media has significantly reshaped the landscape of Islamic da’wah, leading to a redefinition of piety and religious expressions within contemporary Muslim societies. This research explores how mediatization and branding strategies reframe Islamic da’wah through the production of digital content on platforms such as Instagram, TikTok, YouTube, and Spotify. The study aims to critically analyze how elements of media logic speed, aesthetics, emotionality, and interactivity influence the presentation and perception of piety in the digital public sphere. Employing a qualitative descriptive method with an exploratory content analysis approach. Results reveal that piety is not merely internalized but also constructed, commodified, and algorithmically mediated through strategic branding techniques, such as visual identity formation, emotional storytelling, positioning, and audience loyalty cultivation. While digital media expands the reach of da’wah, it also risks reducing spiritual values into performative symbols shaped by market attention and algorithmic virality. This study underscores the need for critical awareness of mediatization effects and offers new insights into how Islamic da’wah must adapt without losing its transformative spiritual essence in an era of digital hyperconnectivity.